O12. Monitor units comparison between TPS and independent software verification system. (September 2016) - Mohlapholi, M.; Mkhize, T.; Moalosi, T.
Abstract : Introduction: In radiation therapy, the treatment planning system (TPS) is used to calculate the monitor units (MUs) needed to deliver a prescribed dose. To avoid any potential errors prior to the start of treatment, quality assurance is performed to verify the MUs with an independent verification system. Commercial MU independent check software such as RadCalc (Lifeline Software Inc., v6.2 Build 5.3) can be used to perform independent MU checks for TPS plans. In this study, we compared MUs calculated with the CMS XiO TPS (v5.1) to the MUs calculated by commercial software RadCalc. Materials and methods: 3D conformal photon beam treatment plans were created for 4 ELEKTA linear accelerator machines (SL15, Precise, Platform and Synergy with Agility head) using the CMS XiO TPS and imported into RadCalc. TPS and independent MU verification system percentage differences were calculated for 3064 fields from a total of 679 patient treatment plans. For integrity, plans were checked for prescribed dose, dose per fraction, number of fractions, machine names and energies, correct MLC shapes, jaws, calculation SSD, depth and MU percentage differences between TPS plan and RadCalc calculations. Results: 679 patient plans were reviewed for a period of five months, calculated MUs were within 10% MU difference limit. For each linac, the average percentage differences were 0.1, −0.9, 0.5 and 0.8% with standard deviations of 2.2, 1.3, 1.8 and 2.0% for SL15, Precise, Platform, and Synergy with Agility head respectively. MUs calculated by RadCalc were comparable to the MUs of the TPS. Conclusion: MUs between the TPS and Independent verification system were well within acceptable tolerances. RadCalc is good enough to perform 3D conformal treatment planning system verification.